Модель підтримки прийняття рішення в проектах захисту складних об’єктів потенційної небезпеки - Сукач, Р. Ю.; Рак, Ю. П. (НТУ "ХПІ", 2016)
У статі виконано процес моделювання складних організаційно-технічних систем та розглянуто можливості використання основ нечіткої логіки, підтримки прийнятих рішень в проектах захисту об‘єктів потенційної небезпеки. Розглянуто, з точки зору переваг і недоліків, використання логічних операцій, а також особливостей і властивостей самого об‘єкта потенційної небезпеки, щодо мінімізації числа вузлових зв‘язків при побудові моделі для оптимальності управління проектом і підвищення стану безпеки життєдіяльності.

The article made the simulation of complex technical-organizational systems in conditions of risk, uncertainty and the impact of the turbulence and the model of decision support to assess the safety and operation of complex object level based on fuzzy logic and considered the possibility of using the foundations of fuzzy logic, support decisions taken in the draft protection of objects of potential danger. It was established that the definition of conjunction and disjunction as «max», and «min», respectively, gives great opportunities to minimize the model, and found that when simplified models, there is an opportunity to come to the point where some units "reduced", that is, some nodes are made to the model at the design stage have no impact on the success of the project of protection of objects of potential danger. Proved that the problem to be solved within the framework for building complex object models in design-oriented project management protection facilities need to use the potential danger disjunction and conjunction formally presented in the form of algebraic product and the amount of fuzzy sets, as this does not lead to the loss of nodes and provides conditions that take into account the impact of all input parameters. Considered in terms of advantages and disadvantages of the use of logical operations, as well as the characteristics and properties of the object of potential hazards, to minimize the number of key relationships in the model for optimal project management in assessing and improving the safety of life.
Decision support model in projects of complex objects protection potential danger
Keywords: ризик; нечітка логіка; невизначеність; безпека; надзвичайні ситуації; complex object model; objects of potential danger; risk; fuzzy logic; uncertainty; security; emergency; facility